A study on the performance of two-level exclusive caching - Musoll, Enric; Nemirovsky, Mario (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1999)
This work presents a study on the performance of a level-two cache configured as a victim storage for the evicted lines of the level-one cache. This two-level cache configuration, known as exclusive caching, is evaluated for a wide range of level-one and level-two sizes and associalivily degrees, and the miss ratios of both levels are compared to those of the two-level inclusive caching. Although the two-level exclusive strategy has lower miss ratios than the inclusive one by increasing the effective associativity and capacity, the replacement policy of the exclusive caching organization forces the invalidation of cnlries in the level-two cache, which reduces the benefits of having a victim level-two cache. The effect of these invalidalions on the overall performance of a level-two exclusive caching organization is evaluated. For typical two-level cache configurations in which the level-two cache is direct-mapped, the performance of the exclusive caching is as much as 60% better for code fetches and as much as 75% for data accesses.